Filter Bases and j-Ï‰-Perfect Mappings - S. Ashaea, G.; Yousif, Y. Y. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
This paper consist some new generalizations of some definitions such: j-Ï‰-closure converge to a point, j-Ï‰-closure directed toward a set, almost j-Ï‰-converges to a set, almost j-Ï‰-cluster point, a set j-Ï‰-H-closed relative, j-Ï‰-closure continuous mappings, j-Ï‰-weakly continuous mappings, j-Ï‰-compact mappings, j-Ï‰-rigid a set, almost j-Ï‰-closed mappings and j-Ï‰-perfect mappings. Also, we prove several results concerning it, where j ÃŽq, Î´,a, pre, b, b.